Acceleration and Gravitational Acceleration Experiments in the Phyphox Virtual Laboratory - Hanifah Qurro Taayyun; Lia Agustina; Lutfi Saoqi Billah; Muhamad Miftah; Adam Malik (Sunan Kalijaga Journal of Physics, 2023)
This study aims to prove the relationship between 2 variables, namely the dependent variable (absolute acceleration) and the independent variable (height) in the acceleration experiment with the acceleration of gravity using the phypox virtual laboratory. The research method used is a combination method consisting of quantitative research methods and . The combination method can provide strong empirical data in proving 2 variables by using a virtual laboratory phypox as a medium in learning the concept of acceleration with gravitational acceleration. The results of this study show the potential for using a virtual laboratory phypox in proving 2 variables which results in a relationship between the value of altitude and absolute acceleration that is directly proportional